2010
DOI: 10.1142/s0219749910006617
|View full text |Cite
|
Sign up to set email alerts
|

Perfect Teleportation Between Arbitrary Split of Six Partites by a Maximally Genuinely Entangled Six-Qubit State

Abstract: In this paper, we show that any S(S = 1, 2, 3, 4, 5, 6) persons can unite to teleport min(S, 6 - S) qubits to the other 6 - S persons if they a priori share a maximally genuinely entangled six-qubit state introduced by Borras et al. [A. Borras, A. R. Plastino, J. Batle, C. Zander, M. Casas and A. Plastino, J. Phys. A40 (2007) 13407]. Also, explicit protocols for perfectly teleporting arbitrary one-qubit state, two-qubit state as well as three-qubit state between arbitrary split of six partites are constructed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…QIS was first confirmed in 1999 using the three-qubit Greenberger-Horne-Zeilinger (GHZ) state [12]. Several multipartite entangled states like the GHZ states [16], the genuinely entangled six-qubit state [17], the modified W states [18,19], the magnon state [20], the cluster states [21,22] and the AKLT states [23] have been utilized for carrying out several quantum tasks. In 2008, Murlidharan and Panigrahi showed that the cluster state can be utilized for QIS [24].…”
Section: Introductionmentioning
confidence: 99%
“…QIS was first confirmed in 1999 using the three-qubit Greenberger-Horne-Zeilinger (GHZ) state [12]. Several multipartite entangled states like the GHZ states [16], the genuinely entangled six-qubit state [17], the modified W states [18,19], the magnon state [20], the cluster states [21,22] and the AKLT states [23] have been utilized for carrying out several quantum tasks. In 2008, Murlidharan and Panigrahi showed that the cluster state can be utilized for QIS [24].…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, works where instead of EPR pairs, more complex states are used as quantum channels. One qubit teleportation protocols are presented in [16] and [17], where GHZ states are employed, while in [18] a maximally entangled six-qubit state is used to teleport an arbitrary three-qubit state (see [19] for a scheme of controlled telepor-tation). In all these cases, the swapping operations that materialize the teleportation correspond to Bell measurements, that is, measurements in a bipartite entangled basis.…”
Section: Introductionmentioning
confidence: 99%
“…that has shown some excellent properties in perfect teleportation 37 and quantum secret sharing. 8 Our protocol allows three participants to compute the summation of their inputs without the help of a trusted third party and preserve the privacy of their inputs, respectively.…”
Section: Introductionmentioning
confidence: 99%